أثر التهريب الجمركي على التنمية الاقتصادية في الجزائر وضرورة التحول نحو الاندماج المغاربي كخيار استراتيجي - طالب, فاطمة; يوسفي, رشيد (Université de M'sila, 2017)
Customs smuggling is one of the most dangerous economic crimes it is A copy of images going out on foreign trade policy and tools.That would negative impact on the emerging institutions and distorts fair competition laws also discourage every desire in the investment and impedes economic and social development, but has political overtones and implications, security, health and agricultural. And in order to eliminate the illegal trade across the border, it took a set of protective measures and repressive with the participation of actors in the field and the state to ensure development, which has long advocated by the border areas,To remain Maghreb economic integration strategic option that ensures the Job Opportunities filled and improve living standards and reduce poverty and is what allows the absorption of smuggling movements.
Keywords: customs smuggling, economic development, Maghreb integration.